Laser Metal Deposition of Ultra-Fine Duplex AlCrFe2Ni2-Based High-Entropy Alloy - Molina, Veronica Rocio; Weisheit, Andreas; Gein, Sergej; Hecht, Ulrike; Vogiatzief, Dimitrios (Frontiers in Materials, 2020)
A duplex, nano-scale Co-free High Entropy Alloy (HEA) based on AlCrFe2Ni2 was processed by means of Laser Metal Deposition (LMD). Process parameters in various beam diameter configurations as well as deposition strategies were developed while the alloy microstructure was investigated in as-built and heat treated condition. Interlayer regions present a duplex microstructure composed of ultra-fine FCC-platelets nucleated in nano-scale structured BCC phase. Rapid cooling during LMD induces the decomposition of the BCC phase into ordered and disordered nano-scaled structures. The hard and brittle BCC phase yields a high crack susceptibility during rapid cooling in the LMD-process. A suitable processing strategy paired with a post-processing heat treatment was developed to solve this challenge. After heat treatment at 900°C and 6 hours annealing time with subsequent furnace cooling, the material presented a homogeneous duplex ultra-fine FCC/BCC microstructure and high flexural strength values (2310 MPa) compared to a heat treated cast duplex-steel (1720 MPa), while maintaining excellent ductility (no failure at 14% bending).